MENGEMBANGKAN BUDAYA BACA TULIS SEBAGAI PROSES MEMBENTUK KARAKTER - Endang Fatmawati (Central Library of Universitas Sebelas Maret, 2017)
A strong correlation exists between reading ability and writing ability. Readingis the window of the world. To produce quality writing then requires the process ofinternalization of knowledge by reading. Reading can build a person’s character,ranging from the appearance of taste, then there is interest, created habits, untilfinally formed the character of reading. Subsequently writing becomes a process ofexternalization of knowledge, from what is thought then poured it into writing. Writingmedia can be either printed documents or through online documents. Thus, writing isessentially a process of thinking. Critical thinking and problem-solving skills are theoutputs of competence that a person must have after he reads.